2014
DOI: 10.1017/s2040174413000512
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal betamethasone increases vascular reactivity to endothelin-1 by upregulation of CD38/cADPR signaling

Abstract: Antenatal steroid administration is associated with hypertension in adult life; however, the mechanisms underlying this phenomenon are unclear. The aim of this study was to further characterize the effects of antenatal glucocorticoid exposure on the endothelin (ET-1) system, specifically to ascertain the role of the cyclic adenosine diphosphate ribose (cADPR)/ryanodine receptor pathway in the increased sensitivity to ET-1 observed in the offspring exposed to antenatal glucocorticoids. Pregnant sheep were rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…[8][9][10][11] Animal models have shown that antenatal glucocorticoids exposure can lead to hypertension and arterial stiffness in later life periods beyond childhood. [8][9][10][11] As a surrogate end point for vascular risk, vascular contractility is closely related to occurrence and progress of many vascular diseases, particularly hypertension. Of critical importance, a number of studies in laboratory animals indicated antenatal dexamethasone treatment impairs vascular contractility in adult offspring 10,11 ; however, limited information is currently available regarding the underlying mechanisms.…”
Section: • Supplemental Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Animal models have shown that antenatal glucocorticoids exposure can lead to hypertension and arterial stiffness in later life periods beyond childhood. [8][9][10][11] As a surrogate end point for vascular risk, vascular contractility is closely related to occurrence and progress of many vascular diseases, particularly hypertension. Of critical importance, a number of studies in laboratory animals indicated antenatal dexamethasone treatment impairs vascular contractility in adult offspring 10,11 ; however, limited information is currently available regarding the underlying mechanisms.…”
Section: • Supplemental Materialsmentioning
confidence: 99%
“…[8][9][10][11] As a surrogate end point for vascular risk, vascular contractility is closely related to occurrence and progress of many vascular diseases, particularly hypertension. Of critical importance, a number of studies in laboratory animals indicated antenatal dexamethasone treatment impairs vascular contractility in adult offspring 10,11 ; however, limited information is currently available regarding the underlying mechanisms. As a dominant cell type that constitutes the vascular wall, vascular smooth muscle cells (SMCs) are key initiators of vascular contractility.…”
Section: • Supplemental Materialsmentioning
confidence: 99%
“… 113 Glucocorticoids increase the sensitivity of blood vessels to endothelium-derived vasoconstrictors, such as catecholamines and endothelin-1. 114 Moreover, glucocorticoids can promote AS development by promoting insulin resistance, dyslipidemia, and hypertension. Glucocorticoids increase the levels of procoagulant factors, mainly including factors VIII, IX, and von Willebrand factor, and impaired fibrinolysis, mainly including plasminogen activator inhibitor-1.…”
Section: Neuroendocrine Disorders and Asmentioning
confidence: 99%
“…The role of retinoic acid in modulating CD38 expression and cADPR levels in many cell types has been investigated extensively [ 32 , 83 ]. Betamethasone, another hormone, administered antenatally in sheep model leads to increased CD38 expression and contributes to postnatal hypertension suggesting a potential augmenting effect of CD38 in peripheral vascular resistance [ 84 ].…”
Section: Regulation Of Cd38 Expression In Asm Cells: Role Of Transmentioning
confidence: 99%